A case of Brugada phenocopy unmasked following giant Asian honey bee stings - H. R. K. K. Maddumabandara; A. Rajaratnam; K. D. Ellepola; S. Bowattage (Sri Lanka College of Internal Medicine, 2024)
This case report details a rare occurrence of Brugada phenocopy (type 1 Brugada electrocardiographic pattern) precipitated following giant Asian honey bee (Apis dorsata) stings in a previously healthy Sri Lankan male. The patient had an uneventful course. While similar ECG patterns can arise from non-genetic factors, Giant Asian honey bee sting as a causal factor is exceedingly unusual and unreported previously. This case adds to the spectrum of cardiac manifestations of Hymenopteran venom highlighting the requirement for close cardiac monitoring and clinical vigilance in these patients.